Análise institucional de um hospital universitário de Minas Gerais: abordagem sócio-histórica do período de 1928 a 2020 - Maria Valdirene Martins (2023)
The Hospital das Clínicas of the Federal University of Minas Gerais (HC/UFMG) was donated to the Faculty of Medicine of the Federal University of Minas Gerais, in 1931, to serve as a training ground for medical teaching and all throughout its almost century-old history, this through countless transformations. It was therefore decided to study the process of institutionalization of this university hospital in Minas Gerais, with the perspective of proposing the creation of a documentation and memory space of the HC/UFMG, for future studies by new researchers. The research is justified by the importance of the said hospital for the university, for the subjects related to it and for society in general. Additionally, there is a lack of studies identifying historical processes involving one of the oldest hospitals in Minas Gerais. Thus, the general objective of this research was highlighted: to analyze the process of institutionalization of teaching in a university hospital in Minas Gerais, from its creation, in 1928 until 2020. This is a research with a qualitative approach which had as theoretical reference Methodological Institutional Analysis, in its socio-historical aspect, because it allows to understand facts circumscribed in the past and those current by analyzing the dialectical movement between those who are established and those who establish the process institutionalization of the university hospital. The study setting was the HC/UFMG located in Belo Horizonte, Minas Gerais. The data collection technique was carried out through documentary analysis. The results highlighted the correlations of forces and the antagonistic forces that acted to maintain the hospital's mission. Even when the goals were relaxed and reshaped, they acted to maintain the founding institution, the mission that was the reason for its creation. As a contribution to this research, there is a brief report that could contribute to the formulation of a project to create a memory center, as a device that can bring together the different elements that tell the stories of the Hospital and to the production of a video. with the main historical facts analyzed here, from the foundation to the present day. Such an iconographic production could function as a “gateway” to arouse interest in topics concerning the UFMG Hospital das Clínicas. This study highlighted the need and could support the proposal to create a Memory and Documentation Center, since the institution analyzed, although it is almost a century old, does not have space to store, conserve and provide a easy access to documents that tell its story and memory.